2005
DOI: 10.1007/bf02959260
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin contamination in insect damaged seeds of horsegram under storage

Abstract: Studies on one of the protein rich pulses, horsegram (Dolichos biflorus L.) were carried out to know how far these low risk pulses are free from aflatoxin contamination under severe insect infestation in storage. A total of 150 stored seed samples of horsegram were analyzed for the presence of aflatoxins by collecting 25 samples each of undamaged and insect damaged seeds of all the three varieties (PDM-1, PHG-1 and HG-96). More than 33% of insect damaged seed samples were contaminated with aflatoxin B1 and B2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Heavily infested kersting's groundnut grains are consumed by the interviewed farmers. However, there are reports of a strong relation between insect infestation and aflatoxins contamination in some pulses such as horsegram (Reddy, Brijitha, & Raghavender, 2005), grass pea (Reddy & Nusrath, 1983), cowpea, and pigeon pea (Matumba et al, 2017) which are poisonous and contribute to the genesis of primary liver cancer in Africa (Koshio et al, 2017;Peers, Gilman, & Linsell, 1976). It is therefore urgent to assess the presence of mycotoxins in Kersting's groundnut seeds heavily infested with insects and to raise farmers' awareness on the harmful effects of mycotoxins on human health.…”
Section: Discussionmentioning
confidence: 99%
“…Heavily infested kersting's groundnut grains are consumed by the interviewed farmers. However, there are reports of a strong relation between insect infestation and aflatoxins contamination in some pulses such as horsegram (Reddy, Brijitha, & Raghavender, 2005), grass pea (Reddy & Nusrath, 1983), cowpea, and pigeon pea (Matumba et al, 2017) which are poisonous and contribute to the genesis of primary liver cancer in Africa (Koshio et al, 2017;Peers, Gilman, & Linsell, 1976). It is therefore urgent to assess the presence of mycotoxins in Kersting's groundnut seeds heavily infested with insects and to raise farmers' awareness on the harmful effects of mycotoxins on human health.…”
Section: Discussionmentioning
confidence: 99%
“…It is well adapted to low rainfall and high temperature, and thus can be grown in areas where other cereal crops such as wheat or maize would not survive. Pearl millet grain is not as susceptible to mycotoxin contamination as groundnut and cereals like maize and sorghum, but can become contaminated with A. flavus and A. parasiticus (Reddy BN, et al, 2005). Raghavender et al (2008) documented 35 fungal species representing 14 genera in stored pearl millet seed samples harvested during the rainy season, and 30 species belonging to 20 genera were found in pearl millet harvested during the dry season.…”
Section: Pearl Milletmentioning
confidence: 97%
“…Hence, it is grown as a common crop in poor, gravelly soils and in regions of low rainfall. B. N. Reddy et al (2005) examined 25 samples each of stored undamaged and insect-damaged horse gram seeds of three varieties (PDM-1, PHG-1, and HG-96) for aflatoxins. Aflatoxin B1 was observed in both the undamaged and insect-damaged seed samples of all the three varieties of horse gram, with higher levels of aflatoxin B1 (up to 130 gkg −1 ) in insect-damaged seed samples.…”
Section: Horse Grammentioning
confidence: 99%
“…Greengram and horsegram also found susceptible to AFB1 accumulation ranging from 645.8 to 2245.2 and 1134.0 to 4589.6 μg kg −1 . Reddy et al. (2005) first time in India reported up to 130 μg kg −1 of AFB1 on insect‐damaged horsegram seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Greengram and horsegram also found susceptible to AFB1 accumulation ranging from 645.8 to 2245.2 and 1134.0 to 4589.6 lg kg )1 . Reddy et al (2005) first time in India reported up to 130 lg kg )1 of AFB1 on insect-damaged horsegram seeds. Still today, no attempts have been made to study the AFB1 production by A. flavus strains on greengram and horsegram seeds.…”
Section: Discussionmentioning
confidence: 99%